How to use storytelling techniques to better communicate science & policy - Calderazzo, John, author; International Wildlife Ranching Symposium, publisher (Colorado State University. Libraries, 2014)
"Science is the greatest of all adventure stories," says physicist Brian Greene, author of The Elegant Universe. "It's been unfolding for thousands of years as we have sought to understand ourselves and our surroundings ... and needs to be communicated in a manner that captures this drama." Carl Sagan and Neil deGrasse Tyson, the old and new storytelling hosts of Cosmos, would agree. So would Rachel Carson, who used one of the oldest and simplest of all story forms, the fable, to coax her readers into a complicated tale of pesticides, chemistry, and ecological succession. Silent Spring may well be the most influential science book of the last fifty years. More than ever, scientists need to communicate clearly and passionately to the public, the media, and decision-makers. Not everyone can be as articulate as a Jane Goodall or Alan Rabinowitz. But humans across every culture are storytelling animals, and recent communications research suggests that information conveyed in story form activates more parts of the brain than when it is conveyed by bullet point or other non-narrative ways. Even a shy and retiring researcher can learn techniques to find common ground with an audience who will not forget the message. My talk will explore how some of the above media stars have used these sometimes-buried communication strategies--and how you can, too.
Using storytelling to communicate science
Using storytelling techniques to communicate science
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Keywords: Wildlife management -- Congresses; Range management -- Congresses